Age-incidence and prevalence of HIV among intact and circumcised men: an analysis of PHIA surveys in Southern Africa - Michel Garenne (My University, 2022)
The study investigates the statistical relationship between male circumcision and HIV prevalence in Africa, in the context of the Voluntary Medical Male Circumcision (VMMC) campaigns in place since 2008. Data from the Population-based HIV Impact Assessment (PHIA) surveys conducted in African countries in 2017-2018 were utilized. Six countries with high HIV prevalence, low traditional circumcision and large VMMC programs were selected: Eswatini, Lesotho, Malawi, Namibia, Zambia, Zimbabwe. The statistical analysis investigated the relative risk (RR) of HIV prevalence by circumcision status (circumcised vs intact) among men age 20-59, and the age-incidence of HIV in the two groups among men age 20-49, defined as the linear-logistic slope of the relationship between prevalence and age. Results show that the standardized RR was not different from 1 at older ages (50-59): RR = 0.923, 95% CI = 0.769-1.108, P = 0.390. Furthermore, the age-incidence was at least as high or higher among the circumcised groups than among the intact groups. The standardized RR was lower than 1 at younger ages, and this could be explained by selection biases. HIV prevalence at age 40-59 (27.3%) was also the same in the four groups of circumcision status (intact, traditional, medical, unknown). Results matched earlier observations made in South Africa that circumcised and intact men had similar levels of HIV infection. The study questions the current strategy of large scale VMMC campaigns to control the HIV epidemic. These campaigns also raise a number of ethical issues
Keywords: HIV/AIDS; Male circumcision; PHIA survey